Forward - Bohak, Gideon; Harari, Yuval (Jewish Thought, 2025)
It is with great pride that we present the sixth issue of the annual journal, Jewish Thought, sponsored by the Goldstein-Goren International Center for Jewish Thought, at Ben-Gurion University of the Negev. This issue focuses on the topic of “Studies on Jewish Magic.” It consists of 14 articles – 7 in Hebrew and 7 in English. Many of the contributions are based on lectures on this topic given at the seventh annual inter-university conference on Jewish magic, held in memory of Prof. Shaul Shaked, which took place at Ben-Gurion University of the Negev in June 2022 under the auspices of the center. The conference was organized by Prof. Yuval Harari from Ben-Gurion University of the Negev, and Prof. Gideon Bohak from Tel-Aviv University, both of whom were invited to serve as guest editors of this issue. This issue is dedicated to the memory of Prof. Shaul Shaked. Prof. Harari wrote in Hebrew a review of Prof. Shaked's research in the field of Jewish magic that opens this issue. All articles that were submitted underwent a rigorous selection process involving at least two reviewers.